A Genealogy of Inelegant Art: The "De Horrendis Simulachris Deum Trinum et Unum Adumbrantibus" and Its History, with Translation and Commentary - Jenkins, Gary W. (Church history and religious culture, 2020)
In 1567 a short Hungarian treatise employing eight woodcuts attacked the doctrine of the Trinity, using the woodcuts to show the enormity of Trinitarian doctrine through the abuses these woodcuts ostensibly represented. But the tract was far more than the woodcuts and their descriptions, but as well contained several swipes at the character of the Trinity as a uniquely Christian doctrine. This essay gives a translation of the tract along with an introduction and commentary on its sources (historical, pictorial, and theological), and the significance of the tract in the history of Antitrinitarianism.